PENYULUHAN PENGENALAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) DI DESA JEJANGKIT MUARA KABUPATEN BATOLA - Muhammad Firman; Budi Hartadi; Idzani Muttaqin; Muhammad Saukani; Nadiya Hijriana (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2016)
Interest Service to the public about solar power plants (PLTS) so that the public understands and knows solar power plant (SPP), increase public understanding of the importance of solar power plants (PLTS) that, while the benefits to be achieved in this activity is to society its target skills and knowledge in assembly and maintenance of a series of solar power plants (PLTS) so that when applied mistakes. Establishment of cooperation between the community, the village government and Studies Program Faculty of Engineering Uniska. As for Tim will add to the experience in training activities assembly and maintenance of solar power plants. The method will be used to achieve the goals that have been implemented are: using the training methods of assembly and maintenance of solar power plants directly with solar panels example demonstrated by the team. So with this training method is expected the participants enthusiastically followed and training materials will absorb well. From the results of the training can be concluded among other things during the training process to be followed can be absorbed 100% or all the participants, 20% of participants who attended or 3 people who want to use solar power for the consumption of their homes by asking what the price of a set of solar power until ready to use and implementation of devotion that will come can be developed into other areas in the vicinity of this devotion, of course, with a bigger budget so that citizens who join the training could be more.